Analysis of Human Characteristics in the Qur'an; Comparative Study of Tafsir Al-Mishbah and Ibn Kathir - Nur Robaniyah; Nusrah, Wahdatun; Ningsih, May Lita Wardiya (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
This scientific article discusses the analysis of human characteristics in the Qur'an through a comparative study between two interpretations of Al-Mishbah and Ibn Kathir. The research method used was a descriptive qualitative analysis with a comparative approach. The purpose of this study was to gain a deeper understanding of human characteristics in the Qur'an, as well as the differences and similarities between the two selected commentaries. The results show that both commentaries have the same view of human characteristics as weak creatures, and are often tempted by lust. However, there are differences in the emphasis between Al-Mishbah and Ibn Kathir in highlighting human traits related to faith, such as devotion, patience, and sincerity. In addition, this study also found that human characteristics in the Qur'an show that humans have a tendency to follow the truth and goodness, but also have the potential to be evil and harm themselves and others. This article can make an important contribution to the development of the understanding of human beings in the Qur'ānic perspective, as well as provide a broader and more detailed view of two well-known commentaries in the Islamic world. Contribution: This study enriches tafsir studies by comparing Al-Mishbah and Ibn Kathir in understanding human characteristics in the Qur'an.